Fitnah dalam Islam: Pengertian, Bahaya, dan Dampaknya bagi Kehidupan Sosial - Rahma Dinda; Rahmatul Riza; Ridwal Trisoni; Muhamad Yahya (Jurnal Budi Pekerti Agama Islam, 2025)
This article discusses the concept of fitnah in Islam, focusing on its definition, forms, risks, and social impacts. Fitnah, referring to false accusations, deceit, and the spreading of misleading information, can pose a serious threat to individual integrity and social balance. The study employs a qualitative descriptive approach with a literature review from classical Islamic texts, Quranic verses, the teachings of the Prophet, and the latest scholarly articles from trusted sources. The findings indicate that fitnah is a significant moral and social violation that can lead to various issues, such as conflicts, defamation, social division, and the loss of trust within society. The study also emphasizes the importance of Islamic ethical principles in preventing and addressing fitnah, especially in the digital age, where information can spread rapidly and widely. The study concludes that preventing fitnah requires an increase in public literacy, more ethical communication, and adherence to Islamic values that emphasize honesty and caution in disseminating information. These efforts are expected to reduce the negative impact of fitnah in social life and foster a more harmonious society.